2016
DOI: 10.1016/j.corsci.2016.05.046
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen trapping in some advanced high strength steels

Abstract: Permeability experiments were used to study hydrogen diffusion and trapping The trapping effect was less significant at a more negative charging potential The lattice diffusion coefficient of hydrogen was measured The densities of reversible hydrogen trap sites was ~ 2 × 10 18 sites cm-2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
60
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(67 citation statements)
references
References 43 publications
7
60
0
Order By: Relevance
“…Traps are usually divided into two types: reversible and irreversible trapping sites depending on their binding energy. Despite the fact that some value of energy (60 kJ/mol) is being sometimes reported to separate reversible and irreversible trapping sites, their properties form a continuum in view of the binding energy and the probability of hydrogen release. Furthermore, reversible character of trapping sites is dependent on the temperature and increases with increasing temperature .…”
Section: Introductionmentioning
confidence: 99%
“…Traps are usually divided into two types: reversible and irreversible trapping sites depending on their binding energy. Despite the fact that some value of energy (60 kJ/mol) is being sometimes reported to separate reversible and irreversible trapping sites, their properties form a continuum in view of the binding energy and the probability of hydrogen release. Furthermore, reversible character of trapping sites is dependent on the temperature and increases with increasing temperature .…”
Section: Introductionmentioning
confidence: 99%
“…Packing distance between atoms affects diffusion speed and saturation limits. Extra space from dislocations, voids, and grain boundaries can be both traps and pathways for diffusing hydrogen [9], [11], [20]. Austenite has a higher hydrogen solubility limit but a slower diffusion rate than ferrite or martensite, making it an effective hydrogen trap [5], [20]- [25].…”
Section: Hydrogen Diffusion In Ahssmentioning
confidence: 99%
“…Extra space from dislocations, voids, and grain boundaries can be both traps and pathways for diffusing hydrogen [9], [11], [20]. Austenite has a higher hydrogen solubility limit but a slower diffusion rate than ferrite or martensite, making it an effective hydrogen trap [5], [20]- [25]. Recent research has indicated that crystalline orientations have an effect on hydrogen diffusion rates [26], and resistance to HE [12].…”
Section: Hydrogen Diffusion In Ahssmentioning
confidence: 99%
“…Figure 1 illustrates the permeation cell [4,86], which is widely used [19,20,22,23,[117][118][119][120][121][122][123][124][125][126][127][128][129][130][131][132][133][134], and was used in this research project. Hydrogen is produced by the applied cathodic potential on the left hand side of the specimen, by the electrochemical cell on the left hand side of the specimen.…”
Section: Permeation Cellmentioning
confidence: 99%